2022
DOI: 10.1101/2022.04.13.488145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systems approach reveals species differences in hepatic stress response capacity

Abstract: In order to minimise the occurrence of unexpected toxicities as a new medicine transitions from the preclinical to clinical phases of development, it is vital to understand fundamental similarities and differences between preclinical species and humans. The well-known difference in sensitivity of mice and rats to acetaminophen (APAP) liver injury has been related to differences in the fraction that is bioactivated to the reactive metabolite N-acetyl-p-benzoquinoneimine (NAPQI). We have used physiologically-bas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…This is particularly relevant in preclinical species that are commonly used in academic research and for the evaluation of drug candidates by the pharmaceutical industry. Recently [63], rats were shown to exhibit a higher hepatic basal NRF2 activity compared with mice, along with a stronger activation of the pathway when the two species were challenged with pharmacokinetically equivalent doses of the hepatotoxin acetaminophen. By extending the analysis of the basal activity of NRF2 to normal liver samples from patients, it was found that mice better reflect the typical NRF2 activity of humans.…”
Section: Trends In Pharmacologicalmentioning
confidence: 99%
“…This is particularly relevant in preclinical species that are commonly used in academic research and for the evaluation of drug candidates by the pharmaceutical industry. Recently [63], rats were shown to exhibit a higher hepatic basal NRF2 activity compared with mice, along with a stronger activation of the pathway when the two species were challenged with pharmacokinetically equivalent doses of the hepatotoxin acetaminophen. By extending the analysis of the basal activity of NRF2 to normal liver samples from patients, it was found that mice better reflect the typical NRF2 activity of humans.…”
Section: Trends In Pharmacologicalmentioning
confidence: 99%